New Genomic Insights into “Entotheonella” Symbionts in Theonella swinhoei: Mixotrophy, Anaerobic Adaptation, Resilience, and Interaction - Liu, Fang; Li, Jinlong; Feng, Guofang; Li, Zhiyong (Frontiers in Microbiology, 2016)
“Entotheonella” (phylum “Tectomicrobia”) is a filamentous symbiont that produces almost all known bioactive compounds derived from the Lithistida sponge Theonella swinhoei. In contrast to the comprehensive knowledge of its secondary metabolism, knowledge of its lifestyle, resilience, and interaction with the sponge host and other symbionts remains rudimentary. In this study, we obtained two “Entotheonella” genomes from T. swinhoei from the South China Sea through metagenome binning, and used a RASTtk pipeline to achieve better genome annotation. The high average nucleotide index values suggested they were the same phylotypes as the two “Entotheonella” phylotypes from T. swinhoei from the Japan Sea. Genomic features related to utilization of various carbon sources, peptidase secretion, CO2 fixation, sulfate reduction, anaerobic respiration, and denitrification indicated the mixotrophic nature of “Entotheonella”. The endospore-forming potential along with metal- and antibiotic resistance indicated “Entotheonella” was highly resilient to harsh conditions. The potential for endospore formation also explained the widespread distribution of “Entotheonella” to some extent. The discovery of Type II (general secretion pathway proteins and the Widespread Colonization Island) and Type VI secretion systems in “Entotheonella” suggested it could secrete extracellular hydrolases, form tight adhesion, act against phagocytes, and kill other prokaryotes. Overall, the newly discovered genomic features suggest “Entotheonella” is a highly competitive member of the symbiotic community of T. swinhoei.